The implementation of the "new" marking system in certain selected schools in the Division of Isabela - Pang, Carmelito D. 1946- (1978)
This study describes the implementation of the "new" marking system in Region 2. The general practice employed by 230 teachers in implementing the "new" marking system consist of ways and criteria for grouping children in their classes; movement between and within groups; modification of corricular content; provisions for individual differences; evaluative measures; school guidance services; and inservice training.